Advanced hepatocellular carcinoma with MET-amplified contained excellent response to crizotinib: a case report - Gu, Yangjun; Xiao, Min; Chen, Zhitao; Li, Qiyong (Frontiers in Oncology, 2023)
Introduction: Hepatocellular carcinoma (HCC) is one of the most lethal tumors all over the world. There are many novel therapeutic strategies tried to prolong the survival of advanced HCC. However, it still lacks therapeutic decision-making biomarkers due to extensive heterogeneity of HCC. Nextgeneration sequencing (NGS) is generally used for treatment decision to help patients benefit from genome-directed targeted. Case presentation: A 56 years-old male with more than 20 years of type-B hepatitis was admitted to our department and underwent laparoscopic hepatic left lateral lobectomy because hepatocellular carcinoma. Unfortunately, tumor recured 1 year later. Though with multiple treatments, the tumor still progressed and invaded the patient's 5th thoracic vertebras, leading to hypoesthesia and hypokinesia below the nipple line plane at 2 years later. NGS identified MET amplification, and Crizotinib, the inhibitor of the MET was recommended. After administering it for one month, tumor markers decreased, and the tumor shrunk obviously. And the patient remains on remission since then. Conclusions: We reported a patient with high MET amplification benefited from its inhibitor which recommended by NGS. It indicated the potential clinical decision support value of NGS and the satisfactory effect of MET inhibitors.